1988
DOI: 10.1287/opre.36.6.826
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Deliberation: Model Management and Group Decision Support

Abstract: Please scroll down for article-it is on subsequent pages With 12,500 members from nearly 90 countries, INFORMS is the largest international association of operations research (O.R.) and analytics professionals and students. INFORMS provides unique networking and learning opportunities for individual professionals, and organizations of all types and sizes, to better understand and use O.R. and analytics tools and methods to transform strategic visions and achieve better outcomes. For more information on INFORMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(84 citation statements)
references
References 24 publications
3
81
0
Order By: Relevance
“…A small screen may increase ranking effects because the narrow view can cause information chunking and users to lose a global perspective of the task, incurring cognitive load (Nunamaker et al 1987(Nunamaker et al , 1988. Numerous studies have documented that the small screens of mobile phones create a serious obstacle to users' navigation activities and perceptions (Chae and Kim 2004); hence, they reduce the effectiveness of the learning experience using mobile devices (Maniar et al 2008), of mobile marketing activities (Shankar et al 2010), of visualization design for mobile devices (Luca 2006), etc.…”
Section: Why Do Ranking Effects Matter?mentioning
confidence: 99%
“…A small screen may increase ranking effects because the narrow view can cause information chunking and users to lose a global perspective of the task, incurring cognitive load (Nunamaker et al 1987(Nunamaker et al , 1988. Numerous studies have documented that the small screens of mobile phones create a serious obstacle to users' navigation activities and perceptions (Chae and Kim 2004); hence, they reduce the effectiveness of the learning experience using mobile devices (Maniar et al 2008), of mobile marketing activities (Shankar et al 2010), of visualization design for mobile devices (Luca 2006), etc.…”
Section: Why Do Ranking Effects Matter?mentioning
confidence: 99%
“…Early trials, however, revealed that people at the time struggled to imagine even the possibility of distributed teamwork. Researchers therefore developed new prototypes based on personal computers connected by a local area network (a radical new technology at the time), and built a first generation of electronic meeting rooms where people could see one another as they worked together and engaged one another through the technology (Figure 4) [51]. Researchers added additional tools to improve the ability of groups to generate, organize, and evaluate ideas [49].…”
Section: Last Research Mile For Group Support Systemsmentioning
confidence: 99%
“…Anonymity influences various types of nonnormative behaviors including arguing (Lee, 2007), lying (Rockman & Northcraft, 2008), risky decisionmaking (Kiesler & Sproull, 1992;Pissarra & Jesuino, 2005), and lowered inhibition in computer-mediated communication (Sosik, Kahai, & Avolio, 1999). Anonymity makes individuals feel less compelled to conform to social norms (Kraemer & King, 1988;Jarvernpaa et al, 1988;Nunamaker, Applegate, & Konsynski, 1988;Connolly, Jessup, & Valacich, 1990;Carte & Chidambaram, 2004). …”
Section: H2bmentioning
confidence: 99%